EXPLORING CRITICAL RACIAL LITERACY IN ENGLISH LANGUAGE TEACHING: EXPERIENCES FROM A TEACHING INTERNSHIP - Nascimento, Ana Karina de Oliveira; Santos, Thiago de Melo Cardoso (Trabalhos em lingüística aplicada, 2025)
ABSTRACT This article is about the teaching internship experience conducted during the master’s program in Languages, in which the course “English Language I” was taught to incoming students of the undergraduate course in Languages (Portuguese/ English), at the Federal University of Sergipe. Alongside covering topics outlined in the course syllabus, focusing on the teaching of English, discussions were held on critical race theory and its place in the educational context, through classroom activities based on critical racial literacy and intersectionality (LADSON BILLINGS, 1998; CRENSHAW, 2004; FERREIRA, 2023). So, we examined our practices as educators and the reflections arising from this experience, which broadened our understanding of ethnic-racial issues, their connections with English language education, and the impacts on contemporary social practices, including exchanges of experiences with the students. Thus, this article aims to share reflections arising from the aforementioned experience. It is a qualitative and interpretive study (MOITA LOPES, 1994; SALDAÑA, 2009), focused on the analysis and interpretation of the meanings constructed during the teaching internship, involving reflections from the researchers’ field diary and records of classroom activities (PARDO, 2019; PAIVA, 2019). The analysis follows the strand of Southern studies (SILVA JR; MATOS, 2019; PENNYCOOK; MAKONI, 2020), which advocate for the inclusion of voices from socially marginalized groups. The results of the experience indicate the relevance of building bridges between academic knowledge production and the social practices of marginalized groups in English language education. RESUMO Este artigo trata de uma experiência de estágio docente realizado durante o mestrado em Letras, no qual foi ministrada a disciplina “Língua Inglesa I” para estudantes ingressantes no curso de graduação em Letras (Português/Inglês) da Universidade Federal de Sergipe. Além de abordar os tópicos da ementa da disciplina, com foco na língua inglesa, foram realizadas discussões sobre a teoria racial crítica e seu desenvolvimento no contexto educacional, por meio de atividades didáticas fundamentadas nas teorias de letramento racial crítico e interseccionalidade (LADSON BILLINGS, 1998; CRENSHAW, 2004; FERREIRA, 2023). Neste contexto, examinamos nossas práticas como docentes e as reflexões advindas dessa experiência, as quais ampliaram nosso entendimento sobre questões étnico-raciais, suas conexões com a educação linguística em língua inglesa e os impactos nas práticas sociais contemporâneas, incluindo as trocas de experiência com os discentes. Assim, este artigo objetiva compartilhar reflexões decorrentes da experiência citada. Trata-se de um estudo qualitativo e interpretativista (MOITA LOPES, 1994; SALDAÑA, 2009), focado na análise dos sentidos construídos durante o estágio docente, envolvendo reflexões do diário de campo dos pesquisadores e registros de atividades de sala de aula (PARDO, 2019; PAIVA, 2019). As análises seguem a corrente de estudos Suleados (SILVA JR; MATOS, 2019; PENNYCOOK; MAKONI, 2020), que preconizam a inclusão de vozes de grupos socialmente marginalizados. Os resultados indicam a relevância da construção de pontes entre a produção de conhecimento acadêmico e as práticas sociais de grupos marginalizados na educação linguística em inglês.